International Financial Statistics , August 2017. (International Financial Statistics; International Financial Statistics, 2017)
This paper discusses currencies' relative importance in international trade and finance, the weights are based on the value of the exports of goods and services of the members issuing these currencies and the balances of their currencies officially held by members of the IMF. From January 1981 to December 1985, the currencies and currency weights of the five members having the largest exports of goods and services during 1975-1979 were the US dollar, 42 percent; deutsche mark, 19 percent; French franc, Japanese yen, and pound sterling, 13 percent each. From January 1986 through December 1990, reflecting the 1980-1984, the weights had changed to US dollar, 42 percent; deutsche mark, 19 percent; Japanese yen, 15 percent; French franc and pound sterling, 12 percent each. From January 1991 to December 1995, reflecting the years 1985-1989, the weights were US dollar, 40 percent; deutsche mark, 21 percent; Japanese yen, 17 percent; French franc and pound sterling, 11 percent each.